Antibacterial and Antiviral Activity of Eucalyptus oil: A Systematic Review - Kambira, Pretty Falena Atmanda; Liliana, Merry; Arfenda, Laurentine Belinda; Marcella, Sherleen (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Eucalyptus sp. is a family member of Myrtaceae, and its oil has been used commercially in the food industry, cosmetics, and pharmaceutical preparation. The fame of Eucalyptus oil rose during the COVID-19 pandemic because several claims have antiviral activity against the coronavirus. Nevertheless, this claim is not scientifically proven and could lead to misinformation among the public. Eucalyptus oil is known to have antibacterial activity against gram-positive and gram-negative bacteria. However, to what extent its effectiveness is has yet to be discovered. Therefore, this study aims to assess eucalyptus oil’s antibacterial and antiviral activity using the Cochrane systematic review. The studies included in the systematic review were retrieved from the PubMed and Science Direct databases. The search query was ("Eucalyptus oil" OR "Eucalyptol") AND ("Antibacterial" OR "Antiviral" OR "MIC"). There are 114 articles identified from the search strategies, and additional 4 articles were found from citation research. After the removal of duplication, 83 articles remained. However, 61 articles were excluded because they did not report the antimicrobial activity of eucalyptus oil. Twenty-two articles were screened for full-text, and 61 were excluded because it does not meet the inclusion criteria. Finally, 16 articles were included in this systematic review. Eucalyptus oil has an antibacterial and antiviral activity that depends on its chemical composition and microbial strains. Therefore, make it a prominent candidate as an antimicrobial and disinfectant compound. However, future clinical study about its mechanism of action is needed.